Anterior mediastinal neuroblastoma in an adult: an additional case of a rare tumor in an unusual location with review of the literature - Katrina Collins; Thomas M. Ulbright; Jessica L. Davis (BMC, 2023)
Abstract Neuroblastoma is rare in the adult population, especially in thoracic or mediastinal locations, with only 25 previously reported cases. We report an additional example of primary thymic neuroblastoma in a previously asymptomatic 71-year-old man with an anterior mediastinal mass who underwent robotic excision with pericardium and adjacent lung. The tumor was a 5.2 cm partially encapsulated, white-tan and rubbery mass with grossly identifiable areas of necrosis (25%) and hemorrhage. Histologically, the specimen showed a rim of adipose tissue and residual thymic tissue with areas of cystic thymic epithelium and prominent lymphoid tissue containing Hassall's corpuscles. The tumor was composed of uniform, round cells with scant cytoplasm and small nuclei with inconspicuous nucleoli set within a background of conspicuous neuropil. Mitotic figures were easily found. By immunohistochemistry, the tumor cells expressed synaptophysin, chromogranin, NKX2.2 (diffuse, nuclear), GFAP (patchy), SMI31 (neurofilament) (focal, cytoplasmic), and TdT (diffuse, nuclear), while lacking expression of CD99, TTF-1, CK 20, MCPyV, PHOX2B, Olig2, OCT3/4, CD45, CD3 and PAX5. S100 protein was negative in the neuroblastic cells, with scattered positive cells in a vague sustentacular-like pattern. Fluorescence in situ hybridization for isochromosome 12p and EWSR1 gene rearrangement were negative. As thymic neuroblastoma is extremely rare in adults, a neuroblastic tumor of germ cell origin (either primary or metastatic) or spread from a sinonasal tract tumor should be excluded because of differing treatments and prognoses. The properties of these rare neoplasms appear similar to olfactory neuroblastoma rather than pediatric-type neuroblastoma.